Heterophase Interface Deformation in Al‐Cu‐Li: Heterophase Interface Dominated Deformation and Mechanical Properties in Al‐Cu‐Li Alloys (Adv. Theory Simul. 6/2021). Issue 6 (5th June 2021) - Wang, Shuo; Zhang, Chi; Li, Xin; Wang, Junsheng
Abstract : In article number 2100059, Junsheng Wang and co‐workers report that the heterophase interfaces in Al‐Li alloys show the generalized stacking fault energy (GSFE) decreasing from the middle of δ'‐Al3 Li/θ'‐Al2 Cu/δ'‐Al3 Li composite structures to the edge, leading to interplanar slip along the [001] direction at relatively low shear stress. This interface‐mediated plasticity within the ultrafine δ'/θ'/δ' composite precipitate is expected to solve the origin of strength‐ductility conflicts in future Al‐Li alloy design.